2011
DOI: 10.1590/s0102-311x2011001000013
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index in individuals with HIV infection and factors associated with thinness and overweight/obesity

Abstract: A cross-sectional study was conducted using body mass index (BMI) to estimate the prevalence of thinness and overweight/obesity and associated factors in 2,018 individuals with HIV/AIDS attending health services referral centers. The dependent variable was classified as thinness, overweight/obesity and eutrophy. Multinomial logistic regression analyses were performed considering eutrophy as the reference level. The prevalence of thinness was 8.8% and of overweight/obesity, 32.1%. The variables associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
31
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 30 publications
13
31
1
5
Order By: Relevance
“…The estimated gross prevalence of undernourishment among HIV/AIDS individuals in this study (7.3%) is similar to the figure found by Mariz et al 22 (8.8% for both sexes), and higher than the one observed by Giudici et al 16 (5.4%), from a study carried out in the same health care network. Other Brazilian studies present prevalences ranging from 1.5% to 5.9% among men, and 3.7% to 9.8% among women 15,16,17,23 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The estimated gross prevalence of undernourishment among HIV/AIDS individuals in this study (7.3%) is similar to the figure found by Mariz et al 22 (8.8% for both sexes), and higher than the one observed by Giudici et al 16 (5.4%), from a study carried out in the same health care network. Other Brazilian studies present prevalences ranging from 1.5% to 5.9% among men, and 3.7% to 9.8% among women 15,16,17,23 .…”
Section: Discussionsupporting
confidence: 89%
“…The complexity of HIV infection and its consequences reinforce the need of health-related actions to maintain the nutritional status of this group of patients. As the subjects of most Brazilian studies on this matter are patients of one single clinic, 13,14,17,18,19,20,21 and few include a higher number of clinics connected to a health care network 15,16,22,23 , the investigations on the nutritional status of HIV/ AIDS individuals, particularly those focusing on undernourishment, in a sample of patients attended in a public healthcare network with facilities broadly distributed over a geographic area, such as the one of the city of São Paulo, Brazil, may contribute for the understanding of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…It can be justified by the fact that all patients use NRTI, which is a drug class that has been named in studies as the main cause for lipodystrophy through the induction of adipocyte apoptosis due to mitochondrial toxicity 24 . Some recent researches conclude the use of HAART is not the only determinant of these changes in the nutritional profile (despite their direct association with adipose tissue and insulin resistance), but rather their sum with genetic, environmental and nutritional factors 25 . The prevalence of clinical dystrophy in this study was similar to the one found in another national study of similar size 23 .…”
Section: Rev Bras Epidemiol Jul-set 2017; 20(3): 526-536mentioning
confidence: 99%
“…This agrees with the reports that demonstrated an association between anemia and weight changes in HIV subjects. [25,26] This demonstrated that anemia was a risk factor of underweight irrespective of the setting in which underweight occurred.…”
Section: Discussionmentioning
confidence: 97%